1980
DOI: 10.1002/j.1879-3479.1980.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids in Women with Liver Cirrhosis

Abstract: Eighteen women with hepatic cirrhosis were examined for plasma levels of testosterone, estrone, estradiol, progesterone and sex hormone binding globulin. For eight who were amenorrheic, with advanced liver cirrhosis and ascites, the reduction of testosterone and rise in estrone and sex hormone binding globulin concentrations were significant. Plasma extradiol and progesterone were lower than normal levels, but the differences were not statistically significant. The other ten patients were menstruating (mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As in chronic alcoholic men with and without liver damage (18,19) and in women with nonalcoholic cirrhosis (42), plasma concentrations of estrone were increased in the patients studied. It is possible that the high plasma estrone levels contributed through negative feedback regulation to the inhibition of gonadotropin secretion in these patients.…”
Section: Discussionmentioning
confidence: 79%
“…As in chronic alcoholic men with and without liver damage (18,19) and in women with nonalcoholic cirrhosis (42), plasma concentrations of estrone were increased in the patients studied. It is possible that the high plasma estrone levels contributed through negative feedback regulation to the inhibition of gonadotropin secretion in these patients.…”
Section: Discussionmentioning
confidence: 79%
“…Gluud et al showed that the ratio of estrogen to testosterone increases with declining liver function 35. Shaaban et al also reported increased estrogen levels in the patients with chronic liver disease 36. Long‐term exposure to the high levels of estrogen seen in the patients with chronic liver disease may be linked to the increased risk of development of de novo breast cancer.…”
Section: Discussionmentioning
confidence: 99%